Monetary policy transmission during financial crises: An empirical analysis - Tatjana Dahlhaus (Bank of Canada, 2014)
This paper studies the effects of a monetary policy expansion in the United States during times of high financial stress. The analysis is carried out by introducing a smooth transition factor model where the transition between states "normal" and high financial stress) depends on a financial conditions index. Employing a quarterly data set over the period 1970Q1 to 2009Q2 containing 108 U.S. macroeconomic and financial time series, I find that a monetary policy shock during periods of high financial stress has stronger and more persistent effects on macroeconomic variables such as output, consumption, and investment than it has during "normal" times. Differences in effects among the regimes seem to originate from non-linearities in the credit channel. – – L'auteure étudie les effets d'une politique monétaire expansionniste aux États-Unis en périodes de fortes tensions financières. Pour procéder à son analyse, elle élabore un modèle factoriel à transition lisse dans lequel le passage d'un état à l'autre (d'une situation « normale » à un régime de fortes tensions) dépend d'un indice des conditions financières. À partir de données trimestrielles allant du premier trimestre de 1970 au deuxième trimestre de 2009, soit 108 séries chronologiques de données macroéconomiques et financières américaines, l'auteure observe qu'un choc de politique monétaire a des répercussions plus importantes et persistantes sur des variables macroéconomiques comme la production, la consommation et l'investissement s'il survient en période de fortes tensions plutôt que lorsque la conjoncture est « normale ». L'incidence différente selon le régime (« normal » / fortes tensions) semble attribuable à la non-linéarité du canal du crédit par lequel se transmettent les mesures de politique monétaire.
Keywords: C11; C32; E32; E44; G01; 330; Financial markets; Econometric and statistical methods; Transmission of monetary policy